PENGGUNAAN BATU PECAH EX. MORAMO (FULL CRUSHER) SEBAGAI MATERIAL CEMENT TREATED BASE (CTB) PADA KONSTRUKSI JALAN - Juprianto Juprianto; Romy S. E. Tamburaka; Sulha Sulha (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2018)
Abstract In line with the rate of population growth in a region, the function of a road is very important as a land transportation infrastructure especially for the continuity of the distribution of goods and services, and as a factor supporting the rate of economic growth. In order for transportation to run smoothly, adequate transportation facilities and infrastructure are needed,the purpose of this study was to determine the characteristics of mountain materials Sanggulaa Village, Kec. Moramo, Kab. South Konawe as a mixture of Cement Treated Base (CTB). Find out the compressive test strength ofcompressive strength of Cement Treated Base (CTB) in cement variations 3 - 5% with a45-55 kg / cm2, which refers to the General Specifications of Bina Marga 2010, Revision 3 (Division 5). This test is a research study by examining Ex.Moramo broken stone material and collecting data processing results in the form of a written summary supported by literature studies,the results showed the characteristics of broken stone material in Sanggulaa Village, Kec. Moramo, Kab. South Konawe is suitable to be used as a mixture of Cement Treated Base in accordance with the test results that meet the requirements in accordance with the General Standards of Bina Marga 2010, Revised 3 (Division 5) and show an average Abrasion test data of 28.19%, and Results of the Compressive Strength that meet the 2010 General Specifications of Bina Marga Specifications Revision 3 (Division 5) 3.5% cement content with a value of Compressive Strength 53.08 kg / cm2.  Abstrak Sejalan dengan laju pertumbuhan penduduk di suatu wilayah, maka fungsi sebuah jalan sangat penting sebagai prasarana perhubungan darat terutama untuk kesinambungan distribusi barang dan jasa, serta sebagai faktor penunjang laju pertumbuhan ekonomi. Agar transportasi berjalan lancar, diperlukan sarana dan prasarana transportasi yang memadai pula.tujuan dari penelitian ini adalah mengetahui karakteristik  Material gunung Desa Sanggulaa, Kec. Moramo, Kab. Konawe Selatan sebagai bahan campur Cement Treated Base (CTB).Mengetahui kuat uji tekan Cement Treated Base (CTB) pada variasi semen 3 – 5 % dengan nilai Kuat Tekan 45-55 kg/cm2, yang mengacu pada Spesifikasi Umum Bina Marga 2010,Revisi 3 (Divisi 5). Pengujian ini merupakan studi penelitian dengan melakukan pemeriksaan terhadap material batu pecah Ex.Moramo serta mengumpulkan hasil-hasil pengolahan data dalam bentuk rangkuman tulisan yang di dukung dengan studi literature,hasil penelitian menunjukkan karakteristik dari material batu pecah Desa Sanggulaa, Kec. Moramo, Kab. Konawe Selatan layak digunakan sebagai campuran lapis pondasi Agregat Semen (Cement Treated Base) sesuai dengan hasil pengujian yang memenuhi syarat sesuai Standar Spesifikasi Umum Bina Marga 2010, Revisi 3 (Divisi 5) dan menunjukkan data pengujian Abrasi Rata-rata 28,19 %, dan hasil Kuat Tekan yang memenuhi standar Spesifikasi Umum Bina Marga 2010 Revisi 3 (Divisi 5) kadar semen 3,5 % dengan nilai Kuat Tekan 53,08 kg/cm2.